Checkpoint Inhibition for Metastatic Urothelial Carcinoma After Chemotherapy—Real-World Clinical Impressions and Comparative Review of the Literature - Fuhrmann, Christian; Struck, Julian P.; Ivanyi, Philipp; Kramer, Mario W.; Hupe, Marie C.; Hensen, Bennet; Fürschke, Alexander; Peters, Inga; Merseburger, Axel S.; Kuczyk, Markus A.; von Klot, Christoph-A. J. (Frontiers in Oncology, 2020)
Background: The introduction of checkpoint inhibitors is a long-awaited new option for a urothelial cancer with a poor prognosis. Apart from clinical studies, the data on real world experience is scarce. Methods: Patients for monotherapy with either Atezolizumab, Nivolumab or Pembrolizumab after chemotherapy were included. Adverse events and immune related adverse events as well as survival data and imaging analyses were recorded in a prospectively designed multi-center data base. Duration of response, progression free survival (PFS) and overall survival (OS) were estimated with the Kaplan-Meier method. Results: A total of 17 patients were included. The median follow-up was 5.8 months (range, 0.7 - 29.8 months). Median PFS was 5.7 months (95% CI, 2.3 - NA months). Median OS for all patients was 8.3 months (95% CI, 3.4 - NA months). Overall response rate (ORR) was 23.5% (4 out of 17 patients). Adverse events were recorded in 11 (64.7%) of patients. Higher grade adverse events (≥Grade 3) were present in 4 (23.5%) patients. No therapy related deaths occurred during the observation period. A total of 7 (41.2%) patients had adverse events that were considered to be immune related. Conclusion: Our real-world clinical series confirms an objective response for about every fifth patient, promising OS and a low incidence for severe adverse events (≥Grade 3).